Problem-based Learning (PBL) effects through blended learning on collaborative ability of biology students - Regina, Angel; Yustina, Yustina; Daryanes, Febblina (Universitas Negeri Padang, 2023)
This research aims to determine the effect of Problem-based Learning (PBL) through blended on students' collaborative abilities in excretion system. This research was conducted at one of High School in Riau, 2021/2022 academic year. This research type is quasi-experiment using questionnaires and observation sheets. The parameters used are students' collaborative abilities, with indicators: working productively, respecting opinions, compromise, and responsibility. Result of collaborative ability in the control class was 48.33 (not good), and in the experimental class it was 82.62 (good). Highest indicator of collaborative ability is responsibility, and the lowest score is compromising. The conclusion is PBL through blended has an effect on students' collaborative abilities.